2021
DOI: 10.14245/ns.2040744.372
|View full text |Cite
|
Sign up to set email alerts
|

Lordosis Distribution Index in Short-Segment Lumbar Spine Fusion – Can Ideal Lordosis Reduce Revision Surgery and Iatrogenic Deformity?

Abstract: Objective: The demand for spinal fusion is increasing, with concurrent reports of iatrogenic adult spinal deformity (flatback deformity) possibly due to inappropriate lordosis distribution. This distribution is assessed using the lordosis distribution index (LDI) which describes the upper and lower arc lordosis ratio. Maldistributed LDI has been associated to adjacent segment disease following interbody fusion, although correlation to later-stage deformity is yet to be assessed. We therefore aimed to investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 40 publications
0
22
0
Order By: Relevance
“…Second, the PI values of patients are widely distributed, and the characteristics of the correlation with LL or PT may differ depending on the range of PI values. 26 But in our study, additional research could not be conducted due to the small number of the patients. If analysis according to this PI distribution is added in the future, more clear results could be derived.…”
Section: Discussionmentioning
confidence: 87%
“…Second, the PI values of patients are widely distributed, and the characteristics of the correlation with LL or PT may differ depending on the range of PI values. 26 But in our study, additional research could not be conducted due to the small number of the patients. If analysis according to this PI distribution is added in the future, more clear results could be derived.…”
Section: Discussionmentioning
confidence: 87%
“…However, as shown in Table 5, patients with ASD showed significantly more decrease in residual lumbar lordosis than those without ASD (16.4° vs −1.0°), indicating that this compensation might exert more pressure in adjacent segments and be related to ASD. Previous studies also reported that an abnormal lordosis distribution index (LDI) could increase the stress of adjacent segments 32–34 . Zheng et al 35 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies also reported that an abnormal lordosis distribution index (LDI) could increase the stress of adjacent segments. 32 , 33 , 34 Zheng et al . 35 found that patients with moderate postoperative LDI showed the lowest risk to develop ASD after L4‐S1 posterior lumbar interbody fusion, while the patients with low LDI were at higher risk to develop ASD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of large cages also allows greater lordosis to be achieved especially in the lower lumbar segments thus, improve the lordosis distribution index and reduce the risks of revision surgery in the future. 25 There is an increasing interest in 3D-printed titanium cages in lumbar spinal fusion. We used 3D-printed titanium cages in our cohort of patients.…”
Section: Discussionmentioning
confidence: 99%